Pengaruh Pemberian Mikoriza Vesikula Arbuskula (MVA) Campuran terhadap Kemunculan Penyakit Layu Fusarium pada Tanaman Melon (Cucumis melo L.) - Najmah Farhati; Purnomowati Purnomowati; Uki Dwiputranto (Fakultas Biologi | Universitas Jenderal Soedirman, 2017)
Melon (Cucumis melo L.) has economic potential to be cultivated because the fruit contains protein, fat, carbohydrate, calcium, phosphor, fiber, iron, vitamin A, vitamin B1, vitamin B2, vitamin C, and niacin. Fusarium wilt caused by Fusarium oxysporum will decrease melon crop production. One of controlling method to Fusarium wilt diseases on melon plants which safe for environtmental by using biological control. One of microorganisms which can be biological control agent is Vesicular Arbuscular Mycorrhiza (VAM). This research use experimental method with a Completely Randomized Design (CRD). The experimental treatment consists of two types of treatment which combine 5 doses of VAM mixture ( 0 g/plant, 10 g/plant, 12,5 g/plant, 15 g/plant, 17,5 g/plant) and two inoculation method VAM is inoculated when seeds are planted and inoculation when the seedlings are replanted. Each treatment was repeated 3 times and each unit consist of three plant, so there are 30 units of experiments or 90 plants. The main variabels are observed consist of the incubation periode of the disease and the intensity of fusarium wilt and the supporting variabels consist of pH, temperature, humidity, and the scale of infection. The mixed MVA 15 g/plant dosage inoculated when seeds are planted and 15 g/plant dosage inoculated when the seedlings are replanted is the most effective to suppress incubation period of Fusarium wilt disease.